IDENTIFICATION OF PHYSICS CONCEPTS PROBLEM IN ANSWERING THE NATIONAL EXAM QUESTIONS AT SENIOR HIGH SCHOOL IN PESISIR SELATAN DISTRICT - Innes Andriani; Silvi Yulia Sari; Yenni Darvina; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2022)
The 21st century is a century with education system that refers to 2013 curriculum which requires teachers to apply learning that is directed at finding out information so that it can help students to have deeper mastery of concepts. The low value of the National Exam (NE) proves that many students have difficulty in working on questions. Therefore, research was carried out to identify problematic physics concepts on NE questions at Senior High School (SMAN) in Pesisir Selatan District. This research is descriptive research with qualitative approach. Population of data in this study was all SMAN that held the NE in Pesisir Selatan District which consisted of 21 schools. Sampling was carried out using Proportionate Stratified Random Sampling technique. The sample of this study was 6 schools that held the NE in SMAN in Pesisir Selatan District. The data in this study were taken from 2018 and 2019 Physics NE data at SMAN in Pesisir Selatan District in education center data (2018) with data collection techniques through documentation studies. Based on this data, it can be obtained the results of identification of problematic physics concepts on NE questions in 2018 with percentage of errors in 6 main materials including Measurement and Kinematics 58.68%; Dynamics 69.33%; Work, Energy and Collision 64.79%; Heat 57.74%; Wave and Light 65.95%; and Magnetism and Core Physics 45.45%. Then, in 2019 it consisted of 4 main materials including Mechanics 58.16%; Wave and Optics 65.87%; Thermodynamics 68.23%; and Magnetism and Modern Physics 57.90%.